2017
DOI: 10.7448/ias.20.1.21290
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of acceptability and willingness to pay for self‐HIV testing in a United States urban neighbourhood with high rates of HIV infection

Abstract: Introduction: Acceptability and willingness to both take and pay for HIV self-tests (HIVSTs) in US neighbourhoods with high rates of HIV infection are not well understood. Methods: We surveyed 1,535 individuals about acceptability and willingness to take and pay for an HIVST in a predominately African American neighbourhood with 3% HIV seroprevalence. We recruited individuals presenting for HIV screening services in a community-based programme. Latent class analysis (LCA) grouped individuals with similar patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Our results suggest that the main barrier to remote testing use was its purchase cost, followed by the length of window period. Existing studies among MSM and other populations have drawn similar conclusions [10,11,3134], but our findings additionally suggest that most people would still prefer HCP to remote testing even if the latter was free and available with a 4-week window period. This is because the majority of participants placed such a high value on HCP testing over and above the specific test characteristics that we investigated.…”
Section: Discussionsupporting
confidence: 84%
“…Our results suggest that the main barrier to remote testing use was its purchase cost, followed by the length of window period. Existing studies among MSM and other populations have drawn similar conclusions [10,11,3134], but our findings additionally suggest that most people would still prefer HCP to remote testing even if the latter was free and available with a 4-week window period. This is because the majority of participants placed such a high value on HCP testing over and above the specific test characteristics that we investigated.…”
Section: Discussionsupporting
confidence: 84%
“…Prior research documents a willingness to self‐test . Nunn and colleagues showed that among the participants surveyed in predominantly African American U.S. neighbourhoods with 3% HIV prevalence, nearly 90% were likely or very likely to accept a free HIV self‐test, and 55% were willing to purchase a test; however, only 23% were willing to pay the market price ($40/test) . Therefore, public sector funding may be critical for the adoption of HIV self‐testing among high‐risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nunn et al investigated the acceptability and the willingness to take and pay for an HIV self-test in a predominately African American neighborhood in the United States. Approximately 90% of respondents were willing to use an HIV self-test and 55% were willing to buy an HIV self-test; however, individuals in the low-risk class were less willing to self-test compared to those with concurrent sexual partners [30]. In another study conducted by Whittington et al to determinate the demand for a hypothetical HIV vaccine in Mexico (Guadalajara), the median WTP value was US$316 [31], which was similar to Cameron et al [26].…”
Section: Discussionmentioning
confidence: 99%